Weddings with uncertain prospects: Mergers under asymmetric information - Thomas Borek; Stefan Buehler; Armin Schmutzler (University of Zurich, Socioeconomic Institute, 2004)
We provide a framework for analyzing bilateral mergers when there is two-sided asymmetric information about firms' types. We show that there is always a no-merger equilibrium where firms do not consent to a merger, irrespective of their type. There may also be a cut-off equilibrium if the expected merger returns satisfy a suitable single crossing condition, which will hold if a firm's merger returns are essentially monotone decreasing in its type. Applying our analysis to the linear Cournot model, we show how the merger pattern depends on the cost effects of mergers, the extent of uncertainty, and the way profits are split. Specifically, we show how increasing uncertainty about competitor types may foster mergers as firms hope for strong rationalization effects.
Keywords: D43; D82; L13; L33; 330; merger; asymmetric information; oligopoly; single crossing; Übernahme; Asymmetrische Information; Theorie